PHYSICAL ACTIVITY DISCUSSIONS AMONG OLDER CANCER SURVIVORS: WHO ARE PROVIDERS ADVISING?. (11th November 2018) - Siembida, E; Kent, E; Bellizzi, K; Wilder Smith, A
Abstract: Discussions and advice regarding physical activity (PA) from healthcare providers promotes PA and its role in improving the physical functioning and well-being of older (age > 65 years) cancer survivors. We aimed to characterize older cancer survivors not discussing and receiving advice on PA from their providers. We used population-based data from the Surveillance, Epidemiology, and End Results-Medicare Health Outcome Survey (SEER-MHOS). Individuals who completed a self-report survey between 2008–2014 and were > 24 months after cancer diagnosis; were diagnosed with histologically-confirmed breast, prostate, or colorectal cancer; visited a healthcare provider in the 12 months preceding survey completion; and reported no difficulties performing activities of daily living (ADLs) were included in the analysis. We analyzed 3, 955 older cancer survivors, of which 59% discussed PA and 74% of those discussing PA received advice, and found that as survivors aged, they were significantly less likely to discuss PA with their providers (OR=0.97, 95% CI 0.96, 0.99) or receive advice about PA (OR=0.96, 95% CI 0.95, 0.98). Survivors' self-reported physical and mental health did not significantly impact the likelihood of PA discussions, but survivors reporting lower physical health were less likely to receive PA advice (OR=0.99, 95% CI 0.98, <1.00). This analysis examines older cancer survivors who reported no difficulties performing ADLs, and as such, represent those with the potential ability to perform and benefit from low-intensity PA. This characterization of survivors not discussing PA provides an opportunity for future work to examine the barriers to implementing PA discussions among older cancer survivors.